The Effect of Pulsatile Flow on bMSC-Derived Endothelial-Like Cells in a Small-Sized Artificial Vessel Made by 3-Dimensional Bioprinting - Kang Woog Lee; Dae-Hyun Kim; Jun Hee Lee; Young-Nam Youn (Stem Cells International)
Replacement of small-sized vessels is still challenging. This study is aimed at investigating the possibility of small-sized artificial vessels made by 3-dimensional bioprinting and the effect of pulsatile flow on bMSC-derived endothelial-like cells. Cells were harvested from rabbit bone marrow and primary cultured with or without growth factors. Endothelial differentiation was confirmed by the Matrigel tube formation assay, Western blot, and qRT-PCR. In addition, embedment of endothelial-like cells in an artificial vessel was made by 3-dimensional bioprinting, and the pulsatile flow was performed. For pumped and nonpumped groups, qRT-PCR was performed on CD31 and VE-cadherin gene expression. Endothelial-like cells showed increased gene expression of CD31 and VE-cadherin, and tube formation is observed at each week. Endothelial-like cells grow well in a small-sized artificial vessel made by 3-dimensional bioprinting and even express higher endothelial cell markers when they undergo pulsatile flow condition. Moreover, the pulsatile flow condition gives a positive effect for cell observation not only on the sodium alginate hydrogel layer but also on the luminal surface of the artificial vessel wall. We have developed an artificial vessel, which is a mixture of cells and carriers using a 3-dimensional bioprinting method, and applied pulsatile flow using a peristaltic pump, and we also demonstrated cell growth and differentiation into endothelial cells. This study suggests guidelines regarding a small-sized artificial vessel in the field of tissue engineering.